Gaya Bahasa dalam Antologi Puisi “Perjamuan Khong Guan” Karya Joko Pinurbo Kajian Stilistika - Dina Hardiani Hilmah Sholihat (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The purpose of this study was to describe the language style, meaning, and figure of speech contained in the book collection of poetry Perjamuan Khong Guan by Joko Pinurbo. The research approach used in this research is a descriptive qualitative approachThe data collection techniques used in this study were literature techniques and note-taking techniques in the form of words, phrases, lines, and poetry stanzas. The results of this study indicate that there are rhetorical and figurative language styles from the 10 poems that the researcher took. The style of language that often appears or is dominantly used in the collection of poetry Perjamuan Khong Guan by Joko Pinurbo is a figurative language style. The style of language is dominated by the use of language styles consisting of personification and metaphorical figure of speech.